Malignant peripheral nerve sheath tumour—A case report. (2019) - A.C., Senthilkumar; Sridharan, S.; Mahendra, B.; Chander, V.
Highlights: Pre-sacral mass presenting with right thigh shooting pain in the setting of Von Recklinghausen. Radiological imaging was crucial in providing a road map pre-op. Mass abutting the internal iliac artery and possibly pressing on the sacral nerve roots. Abstract: Introduction: Malignant peripheral nerve sheath tumors (MPNST) are rare, aggressive sarcomatous tumors that arise from peripheral nerve sheaths and show schwann cell differentiation (Thangadurai, 2017) [1 ]. They commonly arise among patients with neurofibromatosis I and following radiation therapy (Farid et al., 2014). High resolution PET scans confirm the diagnosis and the definitive treatment is surgical excision. Post operative radiotherapy plays an important role in disease free survival rates. Chemotherapy is offered to people who have a systemic disease. Presentation of case: This case report is on a 47 year old lady, a known case of Von Recklinghausen, who complained of a vague mass in the pelvis with recent history of pain to her right thigh. Pelvic examination revealed a vague mass on the right side of her pelvis. She was planned for excision of the mass. Intraoperative findings were consistent with the clinical and radiological findings. She is currently on regular follow-up and disease free. Discussion: MPNSTs are rare tumours that arise in patients with neurofibromatosis I. Mutations at the genetic level is responsible for the development of MPNST. Early presentation, radiological confirmation, aggressive margin free surgery followed by chemoradiation helps in near complete cure of the disease. Conclusion: MPNST are difficult to manage because of their aggressive nature and the limitations in early diagnosis and management. In patients with Von Recklinghausens disease, malignancy must be suspected when a patient presents with the complaints as mentioned in this case report.